Automated Chief Complaints Visualization Using Word Cloud form Textual Data to Enhance Patient Quick Review - Sinprasat, Sittha; Tanphiriyakun, Thiraphat; Yotwongratsamee, Nonpawit (Journal of the Thai Medical Informatics Association, 2022)
Automated chief complaints visualization using word cloud form textual data to enhance patient quick review is one of the internal software development projects of Sriphat Medical Center, Faculty of Medicine, Chiang Mai University. It aims to create a system for classifying some key words of the Chief Complaint and present them in several groups of words. The system is developed as a web application. It was developed with JavaScript for front-end development by using the Vue.JS framework, and Python for backend development. The system is connected to Microsoft SQL Server database. The system is designed and developed to be able to know the numbers of Chief Complaint. For the part of word tokenize, Maximal Matching model was selected. The presentation of data can be divided into 3 groups as follows: 1. Chief Complaint Overall 2. Chief Complaint by Clinic and 3. Chief Complaint by HN. This system was developed for the physicians to know the number of Chief Complaint and can use that information to plan for the future treatment of patients. References วิรัช ศรเลิศล้ำวาณิช. (2536). การตัดคำภาษาไทยในระบบ แปลภาษา.กรุงเทพมหานคร : ศูนย์เทคโนโลยีอิเล็กทรอนิกส์ และคอมพิวเตอร์แห่งชาติ. 50-55 Sanook guru.(2556).โปรแกรมตัดคำภาษาไทย (Thai Word Segmentation).สืบค้น 2 สิงหาคม 2564. จาก https://guru.sanook.com/1530/ วิกานดา ผาพันธ์, และ อัญชนา พิมพิศาล. (2563). การ พยากรณ์ทิศทางของราคาหุ้นรายวันจากข้อความข่าวภาษาไทย โดยใช้วิธีการประมวลผลภาษาธรรมชาติ. วารสารวิทยา ศาสตร์ประยุกต์, 19(1), 59-79. doi:10.14416/j.appsci. 2020.01.006 แอดมินโฮ โอน้อยออก. (2560). ตัดคำภาษาไทยโดย ใช้ Deep learning (AI). สืบค้น 2 สิงหาคม 2564. จาก https://www.patanasongsivilai.com/blog/tudkumthai/ VISTEC-depa AI Research Institute of Thailand. (2564). WangchanBERTa โมเดลประมวลผลภาษาไทย ที่ใหญ่และก้าวหน้าที่สุดในขณะนี้. สืบค้น 2 สิงหาคม 2564. จาก https://medium.com/airesearch-in-th/wangchanbertaโมเดลประมวลผลภาษาไทยที่ใหญ่และก้าวหน้าที่สุดในขณะนี้- d920c27cd433 รตานา ยามาเจริญ. (2562). การวิเคราะห์คำค้น ในรูปแบบ Word cloud เพื่อสนับสนุนงานบริการสารสนเทศของห้อง สมุด(รายงานผลการวิจัย). สำนักทรัพยากรการเรียนรู้ คุณหญิงหลง อรรถกระวีสุนทร, มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตหาดใหญ่